New Mutations in cls Lead to Daptomycin Resistance in a Clinical Vancomycin- and Daptomycin-Resistant Enterococcus faecium Strain - Li, Weiwei; Hu, Jiamin; Li, Ling; Zhang, Mengge; Cui, Qingyu; Ma, Yanan; Su, Hainan; Zhang, Xuhua; Xu, Hai; Wang, Mingyu (Frontiers in Microbiology, 2022)
Daptomycin (DAP), a last-resort antibiotic for treating Gram-positive bacterial infection, has been widely used in the treatment of vancomycin-resistant enterococci (VRE). Resistance to both daptomycin and vancomycin leads to difficulties in controlling infections of enterococci. A clinical multidrug-resistant Enterococcus faecium EF332 strain that shows resistance to both daptomycin and vancomycin was identified, for which resistance mechanisms were investigated in this work. Whole genome sequencing and comparative genomic analysis was performed by third-generation PacBio sequencing, showing that E. faecium EF332 contains four plasmids, including a new multidrug resistant pEF332-2 plasmid. Two vancomycin resistance-conferring gene clusters vanA and vanM were found on this plasmid, making it the second reported vancomycin resistant plasmid containing both clusters. New mutations in chromosomal genes cls and gdpD that respectively encode cardiolipin synthase and glycerophosphoryl diester phosphodiesterase were identified. Their potential roles in leading to daptomycin resistance were further investigated. Through molecular cloning and phenotypic screening, two-dimensional thin layer chromatography, fluorescence surface charge test, and analysis of cardiolipin distribution patterns, we found that mutations in cls decrease surface negative charges of the cell membrane (CM), and led to redistribution of lipids of CM. Both events contribute to the DAP resistance of E. faecium EF332. Mutation in gdpD leads to changes in CM phospholipid compositions, but cannot confer DAP resistance. Neither mutation could result in changes in cellular septa. Therefore, we conclude that the daptomycin resistance of E. faecium EF332 is conferred by new cls mutations. This work reports the genetic basis for vancomycin and daptomycin resistance of a multidrug resistant E. faecium strain, with the finding of new mutations of cls that leads to daptomycin resistance.